Internal Factors Determining MSME Business Performance: A Literature Study - Agus, Agus; Limakrisna, Nandan; Muharram, Hari (Riviera Publishing, 2023)
This research aims to examine the internal factors that determine MSME business performance. This research uses a literature review approach. The data collection technique in this research uses the literature study method. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation, and conclusion. The research results show that the internal factor determining MSME business performance is that MSMEs are essential in developing the national economy. Hence, MSMEs require more attention regarding their business performance. Performance is a result of efforts made both in quality and quantity. The measurement of MSME business performance can be seen from the increase in sales, which is the increase in the number of purchases made by customers for the goods sold. In a business, performance always rises and falls, as does MSME business performance because several internal factors determine it: finance, customers, internal business processes, learning, and growth.